A review of the ichthyofauna of Malaysian peat swamp forest - Aliu, Sule Hussein; Ismail, Ahmad; Azmai, Mohammad Noor Amal (Universiti Putra Malaysia Press, 2016)
A review of literature showed that numerous intensive surveys have been carried out on the ichthyofauna of the peat swamp forests (PSFs) of Malaysia. This review aims to provide a checklist of blackwater fish species in Malaysia from available published literature, and address their economical importance, conservation status and problems of PSFs. A total of 198 peat swamp fish species from 32 families have been recorded in Malaysia. From this number, a total of 114 species from 23 families, representing about 40% of the known fish fauna in Peninsular Malaysia, were recorded from north Selangor PSF. Meanwhile, a total of 49 species belonging to 18 families, 13 species from seven families, 58 species belonging to 19 families, and nine species from five families were recorded from the peat swamps of Perak, Johor, Pahang and East Peninsular Malaysia (parts of Pahang and Terengganu), respectively. Meanwhile, 31 species from 12 families and 40 species belonging to 13 families were recorded from Sabah and Sarawak, respectively. Family Cyprinidae has the highest recorded species, followed by Osphronemidae, Bagridae and Siluridae. The IUCN Red List revealed 12 threatened species facing risk of extinction. The importance of conserving PSFs was outlined and suggestions made in line with the objectives of conservation. Findings from literature revealed that Malaysia's PSFs are rich in fish diversity, contrary to previous belief, and should therefore be conserved and protected to ensure the richness of their fish diversity.